2002
DOI: 10.4161/cc.1.2.115
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Preventive Flavonoid Silibinin Causes Hypophosphorylation of Rb/p107 and Rb2/p130 Via Modulation of Cell Cycle Regulators in Human Prostate Carcinoma DU145 Cells

Abstract: © 2 0 0 2 L a n d e s B i o s c i e n c e . N o t f o r d i s t r i b u t i o n . ABSTRACTPhosphorylation status of retinoblastoma (Rb) and related proteins is important to drive cell cycle progression. In hyperphosphorylated state, they are growth stimulatory, but their hypophosphorylation is growth inhibitory. Here we assessed whether silibinin causes hypophosphorylation of Rb-related proteins as its growth inhibitory response in human prostate cancer (PCA) DU145 cells. Silibinin treatment of cells resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 27 publications
5
40
0
2
Order By: Relevance
“…Silibinin treatments induced strong G 1 arrest (P < 0.001) in DU145 cells in a dose-dependent manner (Fig. 1C), which was consistent with earlier observations (34). Analyses of the results showed that DU145 cells started accumulating in G 1 phase between 12 and 24 h at the expense of a dose-dependent decrease (P < 0.001) in S-phase population.…”
Section: Silibinin Inhibits Cell Growth and Induces G 1 Arrest In Du1supporting
confidence: 80%
“…Silibinin treatments induced strong G 1 arrest (P < 0.001) in DU145 cells in a dose-dependent manner (Fig. 1C), which was consistent with earlier observations (34). Analyses of the results showed that DU145 cells started accumulating in G 1 phase between 12 and 24 h at the expense of a dose-dependent decrease (P < 0.001) in S-phase population.…”
Section: Silibinin Inhibits Cell Growth and Induces G 1 Arrest In Du1supporting
confidence: 80%
“…Recently, several studies with the antioxidant vitamin E and the polyphenolic flavonoid silibinin showed similar results concerning their anti-proliferation effects on PCA cells. The signaling pathway includes elevation in the hypophosphorylated form of pRb at the expense of the phosphorylated form of Rb, reduction at the protein level of CDKs, and cyclin typical to G1 phase of the cell cycle together with enhanced expression of the CDK inhibitor p21 cip1 [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these effects were similar with recently reported effects of cancer-preventive flavionoids, suggesting the link between cancer-preventing and therapeutic phytochemicals. 25,26 In sequence, Rb binds to transcription factor E2F which is critically involved in the control of several S phase requiring proteins including the expression of mini-chromosome maintenance (MCM) family of proteins that regulate DNA replication. Such a mechanistic scenario was also demonstrated by the array data showing that PC-SPES inhibited E2F, MCM2, 5 and 7 expressions (Table 1).…”
Section: Pc-spes Inhibits Cell Proliferation By Modulating P21 Cyclimentioning
confidence: 99%